Spatial ecology of a herd of white-lipped peccaries (Tayassu pecari) in Belize using GPS telemetry: challenges and preliminary results - Hofman, Maarten P. G.; Signer, Johannes; Hayward, Matthew W.; Balkenhol, Niko (THERYA, 2016)
The Maya Mountains are a heavily forested mountain range in Belize and Guatemala supporting high levels of biodiversity. Due to environmental degradation around the range, it is in danger of becoming isolated from the largest contiguous forest in Central America. Forest connectivity in the area is vital for white-lipped peccaries. These social ungulates roam in herds of up to 300 individuals and need large forested areas to sustain populations. The species has not previously been studied in Belize and its distribution, population size, herd dynamics and movement patterns are unknown for the country. We aimed to estimate home range size and investigate movement patterns of the species in southern Belize. We present a preliminary 4-month data set from a herd of ca. 60 animals tracked by an individual fitted with a GPS satellite collar. We evaluated collar performance, habitat preference and movement characteristics, and estimated home range size using a semi-variogram approach, suited for sparse and irregular data. Collar performance was poor, with 38 % of the data not reaching the satellite, and a GPS fix success rate of 11.6 % for the data that did reach the satellite. The semi-variogram home range size was 55.2 km2. We observed a maximum daily movement distance of 3.8 km, and a preferential use of forest habitat over shrubland, savannah and cropland. We calculated a density of 1.09 ind/km2 and make an informed guess of close to 100 herds in the broad-leaf forests of the Maya Mountains. Our study highlights some of the challenges faced when collaring white-lipped peccaries, as well as the performance of GPS-collars in tropical forests. It also provides a first glimpse of the home range and movement behaviour of white-lipped peccaries in Belize.